Genetic Variability and Hetrosis in Cucumber (Cucumis Sativus L.) - Gayathri K (Department of Horticulture, College of Agriculture, 1997)
The present investigation on (Genetic variability and heterosis in cucumber (Cucumis sativus L.)' was conducted at the College of Agriculture, Vellayani, Trivandrum during 1995-97. Twenty two genotypes of cucumber collected from different parts of the country were grown in randomised block design with two replications and assessed the genetic variability of fifteen characters. The genetic parameters like variability, heritability, genetic advance, correlation coefficients and direct and indirect effects of the component traits on yield were estimated. Seven parents were selected based on selection index, crossed in all possible combinations without reciprocals in a 7x7 diallel and produced 21 Fl hybrids. These F1 hybrids were evaluated along with their parents and derived information on general and specific combining ability and heterosis. Significant differences were observed among the 22 genotypes for all the fifteen characters studied. Yield/plant, fruits/plant, average fruit weight and node to first female flower had the highest genotypic coefficient of variation with high heritability and genetic advance. Fruits/plant, average fruit weight, fruit girth and fruit diameter were highly correlated with yield. Fruit girth exerted the maximum